2003
DOI: 10.1046/j.1365-2524.2003.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Who uses welfare benefits advice services in primary care?

Abstract: There is considerable interest among organisations such as primary care trusts and health action zones in commissioning welfare benefits advice services in primary healthcare settings as part of local strategies to reduce health inequalities. However, very little is known about the contribution to health of such services or about the health status of those who use them. The present study reports on a longitudinal study of the contribution to individual health of welfare benefits advice in primary care that has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…Fifteen papers used validated tools to assess whether there was a measurable impact of advice services on health (Memel & Gubbay 1999, Abbott & Hobby 2000, 2002, 2003, Greasley 2003, Langley et al. 2004, Powell et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen papers used validated tools to assess whether there was a measurable impact of advice services on health (Memel & Gubbay 1999, Abbott & Hobby 2000, 2002, 2003, Greasley 2003, Langley et al. 2004, Powell et al.…”
Section: Resultsmentioning
confidence: 99%
“…(2003) categorised these uses as increased spending on essentials such as food; spending to increase mobility, such as taxis; the provision of additional goods and services such as gardeners; spending on large household items such as fridges; and spending on personal items such as presents for grandchildren. Improved mobility was also reported as an outcome of some of the other non‐financial benefits such as disabled parking permits and adaptations to the house (Paris & Player 1993, Abbott & Hobby 2003, Greasley 2003, Toeg 2003, Caiels & Thurston 2005, Moffatt & Scambler 2008, Moffatt & Mackintosh 2009, Moffatt et al. 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to examine this specifically as there was a perception among CAB staff and GPs anecdotally that the service was of particular benefit to patients with mild-to-moderate mental health issues. A number of studies have suggested that welfare advice reduces problems such as anxiety and worry and improves mental health (Abbott and Hobby, 2003;Adams et al, 2006), and may reduce overall use of health services and medicines (Abbott and Hobby, 2003). A number of studies have suggested that welfare advice reduces problems such as anxiety and worry and improves mental health (Abbott and Hobby, 2003;Adams et al, 2006), and may reduce overall use of health services and medicines (Abbott and Hobby, 2003).…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…The service has been advocated as contributing to reducing health inequalities and improving the health of those in poverty, through financial gain. Most studies of such services, however, suggest they are used most frequently by older people, those with disabilities and ethnic minorities, (Coppel et al, 1999;Wiggan and Talbot, 2006;Moffatt and Mackintosh, 2009) and not by those with mental health problems (Abbott and Hobby, 2003). However, there was little robust evidence that they also impact on health (Adams et al, 2006).…”
Section: Introductionmentioning
confidence: 99%